PENGARUH BUDAYA ORGANISASI TERHADAP SEMANGAT KERJA PEGAWAI BAGIAN UMUM SEKRETARIAT DAERAH KABUPATEN BOYOLALI - Jauhari, Slamet (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2015)
The research aims to find out: the influence of organizational culture on employee morale General Affairs Regional Secretariat Boyolali. This research is explanatory. The population in this study are all part of the General Regional Secretariat Boyolali as many as 92 people and all the members of the study population sampled. Data analysis method used is simple regression analysis. Based on the results of this study concluded that the social welfare of the t test obtained t count > t table (12,978 < 1,67), this means that the factor of social welfare effect on employee morale at the General Affairs Regional Secretariat Boyolali. Variables that have the most dominant effect is the well-being with a regression coefficient of 0,746. Keywords: Organizational culture, Morale